Case Report: FOXP3 Mutation in a Patient Presenting With ALPS - Rais, Afef; Mekki, Najla; Fedhila, Faten; Alosaimi, Mohammed Faraj; Ben Khaled, Monia; Zameli, Amal; Agrebi, Nourhen; Sellami, Maryam Kallel; Geha, Raif; Ben-Mustapha, Imen; Barbouche, Mohamed-Ridha (Frontiers in Immunology, 2021)
ALPS and IPEX are two well characterized inborn errors of immunity with immune dysregulation, considered as two master models of monogenic auto-immune diseases. Thus, with autoimmunity as their primary clinical manifestation, these two entities may show clinical overlap. Traditionally, immunological biomarkers are used to establish an accurate differential diagnosis. Herein, we describe a patient who presented with clinical features and biomarkers fulfilling the diagnostic criteria of ALPS. Severe apoptotic defect was also shown in the patient’s cell lines and PHA-activated peripheral blood lymphocytes. Sanger sequencing of the FAS gene did not reveal any causal mutation. NGS screening revealed a novel deleterious variant located in the N terminal repressor domain of FOXP3 but no mutations in the FAS pathway-related genes. TEMRA cells (terminally differentiated effector memory cells re-expressing CD45RA) and PD1 expression were increased arguing in favor of T cell exhaustion that could be induced by unrestrained activation of T effector cells due to Treg deficiency. Moreover, defective FOXP3 observed in the patient could intrinsically induce increased proliferation and resistance to apoptosis in T effector cells. This observation expands the spectrum of FOXP3 deficiency and underscores the role of NGS in detecting mutations that induce overlapping phenotypes among inborn errors of immunity with immune dysregulation. In addition, these findings suggest a potential link between FOXP3 and FAS pathways.